Development of Lactobacillus kimchicus DCY51T-mediated gold nanoparticles for delivery of ginsenoside compound K: in vitro photothermal effects and apoptosis detection in cancer cells - Yeon-Ju Kim; Haribalan Perumalsamy; Josua Markus; Sri Renukadevi Balusamy; Chao Wang; Seong Ho Kang; Seungah Lee; Sang Yong Park; Sung Kim; Verónica Castro-Aceituno; Seung Hyun Kim; Deok Chun Yang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We report a non-covalent loading of ginsenoside compound K (CK) onto our previously reported gold nanoparticles (DCY51T-AuCKNps) through one-pot biosynthesis using a probiotic Lactobacillus kimchicus DCY51T isolated from Korean kimchi. The ginsenoside-loaded gold nanoparticles were characterized by various analytical and spectroscopic techniques such as field emission transmission electron microscopy (FE-TEM), energy-dispersive X-ray (EDX) spectroscopy, elemental mapping, X-ray powder diffraction (XRD), selected area electron diffraction (SAED), Fourier-transform infrared (FTIR) spectroscopy and dynamic light scattering (DLS). Furthermore, drug loading was also determined by liquid chromatography–mass spectrometry (LC–MS). In addition, DCY51T-AuNps and DCY51T-AuCKNps were resistant to aggregation caused by pH variation or a high ionic strength environment. Cell-based study confirmed that DCY51T-AuCKNps exhibited slightly higher cytotoxicity compared to ginsenoside CK treatment in A549 cells (human lung adenocarcinoma cell line) and HT29 (human colorectal adenocarcinoma cell line). Upon laser treatment, DCY51T-AuCKNps showed enhanced cell apoptosis in A549, HT29 and AGS cells (human stomach gastric adenocarcinoma cell line) compared with only DCY51T-AuCKNps treated cells. In conclusion, this preliminary study identified that DCY51T-AuCKNps act as a potent photothermal therapy agents with synergistic chemotherapeutic effects for the treatment of cancer.